Pengaruh Penambahan Bahan Admixture Consol SG terhadap Kuat Tekan Beton - Arifien Nursandah; Satriyo Utomo; Dio Alif Hutama (AGREGAT, 2018)
AbstractConcrete is a building material that is very popularly used in the world of construction services, along with the rapid development of concrete technology has been successfully developed various innovation on additive material in concrete mixes to get good quality concrete. Consol SG is an additive material or admixture which is a product of liquid concrete plasticizers and high water reducing agents by regulating the effect of retarding, can increase workability without increasing water content, reducing water without losing workability, and increasing compressive strength, and chloride free with no damaging on reinforcement. This research used an experimental method in a laboratory with a total of 60 samples of specimens, concrete compressive strength at 28 days with a cylinder diameter of 150 mm high by 300 mm with a variation of Consol SG mixture of 0%, 0.2% and 0.3% with high quality planned f'c = 30 MPa, on the effect of Consol SG addition on the compressive strength of the concrete which is viewed from the variation of Consol SG mixture. The results of the concrete compressive strength value of Consol SG 0.2% is 31.13 MPa (up to 2.54% in terms of normal concrete), for the variation of Consol SG 0.3% mixture of 32.25 MPa (up to 6.22% in terms of normal concrete). While the variation of 0.2% to 0.3% increased by (3.59%). The test of the statistical model used is the Chi-Square test and the T-test using the SPSS software.Keywords: Additive, Consol SG, Compressive Strength of Concrete.AbstrakBeton merupakan bahan bangunan yang sangat populer digunakan dalam dunia jasa konstruksi, seiring pesatnya perkembangan teknologi beton telah berhasil dikembangkan berbagai inovasi bahan tambah dalam campuran beton agar mendapatkan beton yang berkualitas baik. Consol SG adalah bahan tambah admixtures atau additive merupakan produk plasticizer beton cair dan agen pereduksi air yang tinggi dengan mengatur efek perlambatan, dapat meningkatan kemampuan kerja tanpa meningkatkan kadar air, mengurangi air tanpa kehilangan kemampuan kerja, dan meningkatkan kuat tekan, serta bebas klorida yang tidak merusak pada tulangan. Penelitian ini menggunakan metode eksperimen dilaboratorium dengan total benda uji 60 sampel, kuat tekan beton pada umur 28 hari dengan diameter silinder ukuran 150 mm tinggi 300 mm dengan variasi campuran Consol SG sebanyak 0%, 0,2% dan 0,3% dengan mutu yang direncanakan f’c = 30 MPa, pada pengaruh penambahan Consol SG terhadap kuat tekan beton yang ditinjau dari variasi campuran Consol SG. Hasil nilai kuat tekan beton pada campuran Consol SG 0,2% sebesar 31,13 MPa (naik 2,54% ditinjau dari beton normal), untuk variasi campuran Consol SG 0,3% sebesar 32,25 MPa (naik 6,22% ditinjau dari beton normal). Sedangkan variasi 0,2% ke 0,3% naik sebesar (3,59%). Pengujian model statistik yang digunakan adalah uji Chi-Kuadrat dan uji T menggunakan aplikasi SPSS.Kata Kunci: Additive, Consol SG, Kuat Tekan Beton.